Association between serum uric acid levels and cardiovascular events in hospitalized patients with type 2 diabetes - Chang, Zhan (A pilot randomized controlled trial examining the feasibility, acceptability, and efficacy of Adapted Motivational Interviewing for post-operative bariatric surgery patients, 2021)
• Retrospective study of hospitalized type 2 diabetes patients. • Uric acid level in women is associated with cardiovascular events. • Uric acid level in men is not associated with cardiovascular events.